2015
DOI: 10.1063/1.4907608
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbon nanotube length on electron transport in aligned carbon nanotube networks

Abstract: Here we quantify the electron transport properties of aligned carbon nanotube (CNT) networks as a function of the CNT length, where the electrical conductivities may be tuned by up to 10× with anisotropies exceeding 40%. Testing at elevated temperatures demonstrates that the aligned CNT networks have a negative temperature coefficient of resistance, and application of the fluctuation induced tunneling model leads to an activation energy of ≈ 14 meV for electron tunneling at the CNT-CNT junctions. Since the tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 55 publications
7
92
1
Order By: Relevance
“…2b demonstrates, R c plateaus at 0.1 ≤ w ≤ 0.3 and has a value of ∼1 nm for V f = 40% CNTs, a value that is on the same order of the curvature of ripples that are expected to form on the surface of ∼8 nm diameter (∼1.5 nm wall thickness) CNT during buckling, 30,31 indicating that the simulation results are physical for V f ≤ 40% CNTs. A note should be made that R c ∼ 1 nm is on the same order as the variations in the CNT inner and outer diameter that were reported previously, 32 and that such nanoscale surface features can arise through either Stone-Wales or inter-wall defects. [33][34][35][36] To ensure that R c is evaluated for an amount of waviness that is generalizable to other non-stochastic descriptions, e.g.…”
supporting
confidence: 67%
“…2b demonstrates, R c plateaus at 0.1 ≤ w ≤ 0.3 and has a value of ∼1 nm for V f = 40% CNTs, a value that is on the same order of the curvature of ripples that are expected to form on the surface of ∼8 nm diameter (∼1.5 nm wall thickness) CNT during buckling, 30,31 indicating that the simulation results are physical for V f ≤ 40% CNTs. A note should be made that R c ∼ 1 nm is on the same order as the variations in the CNT inner and outer diameter that were reported previously, 32 and that such nanoscale surface features can arise through either Stone-Wales or inter-wall defects. [33][34][35][36] To ensure that R c is evaluated for an amount of waviness that is generalizable to other non-stochastic descriptions, e.g.…”
supporting
confidence: 67%
“…Recent studies have confirmed the thermal conductivity of MWCNTs to be about 3000 W/m K, while that of SWCNTs is above 2000 W/m K (Pradhan et al 2009). Additionally, they exhibit thermal conductivity in longitudinal orientation within the range of 2800-6000 W/m K for single nanotube at ambient temperature (King et al 2010a,b, Lee et al 2015, which is similar to diamond but superior to graphite and CFs, in addition to an aspect ratio in the order of 103. Thus, enhancement in CNTs' thermal conductivity has been attributed to the formation of a percolation network comparable to the same mechanism observed for electrical conductivity Tai 2008, Wang et al 2014a,b).…”
Section: Thermal Conductivity Of Carbon-nanotube-based Pncsmentioning
confidence: 97%
“…The conductivity of phonons in CNTs is induced by several factors including the number of active modes in the phonon, the scattering at the boundary surface, phonons free path length, and the inelastic Umklapp scattering, which is an erratic electron-phonon or phononphonon scattering phenomenon ). Several researches have been conducted on polymer/ CNT thermal conductivity, in addition to other properties (Wang et al 2014a,b, Lee et al 2015. CNTs were reported to have induced enhancement of these properties (Pradhan et al 2009.…”
Section: Thermal Conductivity Of Carbon-nanotube-based Pncsmentioning
confidence: 98%
“…VACNT synthesis (used here as the NPN) proceeded via a thermal catalytic chemical vapor deposition process with a quartz tube furnace of 44 mm inner diameter at atmospheric pressure, which was similar to a previously reported process . Ethylene was used as the carbon source, and water of 600 ppm was added to the helium gas.…”
Section: Methodsmentioning
confidence: 99%